Nematic superconducting state in iron pnictide superconductors - Jun Li (Nature Portfolio, 2017)
Nematic electronic order is rare and its onset often indicates a phase transition. Here, Li et al. report a nematic superconducting state in Ba0.5K0.5Fe2As2 by measuring the angular dependence of the in-plane and out-of-plane magnetoresistivity.